IMPLEMENTASI PROGRAM FORUM ANAK DALAM PENANGGULANGAN KENAKALAN ANAK DI KECAMATAN SUNGAI PINANG KOTA SAMARINDA - Rizki Almira; Enos Paselle (Journal of Policy & Bureaucracy Management, 2020)
In the context of overcoming delinquency in children in Sungai Pinang District, the Government of Sungai Pinang District has implemented a number of activity programs, one of which is the children’s forum program and was confirmed as a child-friendly sub-district in 2015. This research describes the implementation of the children’s forum program in the context of overcoming child delinquency in Sungai Pinang District, Samarinda City and supporting and inhibiting factors by using a qualitative descriptive approach. The results of the study show that the implementation of the children’s forum program has been carried out quite well through the existence of good communication of dispositions and bureaucratic structures even though resources are still constrained, especially in terms of human resource parent’s party and financial factor. The implementation of the children’s forum program is still hampered by the lack of knowledge of parents about children’s forum which causes the lack of participation of parents and children to become managers of the children’s forum program. But the implementation of the children’s forum program is supported by good cross-sectoral cooperation between the Sungai Pinang District Government and various related parties.